2018
DOI: 10.3389/fmicb.2018.03043
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecology on Solar Panels in Berkeley, CA, United States

Abstract: Solar panels can be found practically all over the world and represent a standard surface that can be colonized by microbial communities that are resistant to harsh environmental conditions, including high irradiation, temperature fluctuations and desiccation. These properties make them not only ideal sources of stress-resistant bacteria, but also standard devices to study the microbial communities and their colonization process from different areas of Earth. We report here a comprehensive description of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…The microbial composition is characterized by a set of highly resistant bacterial genera ( Deinococcus, Hymenobacter, Roseomonas ) and fungi ( Alternaria , among others), which are marginally present on the panels at the beginning of the experiment, but increase in frequency and become dominant by the end of the experiment. Some of the most abundant bacterial genera, such as Hymenobacter, Modestobacter and Deinococcus , have in fact previously been isolated from warm, irradiated environments, such as arid soil crusts or hyper‐arid desert soils (Reddy and Garcia‐Pichel, 2013; Busarakam et al ., 2016; Gundlapally and Garcia‐Pichel, 2017), and they have also been reported as frequent taxa inhabiting solar panel surfaces (Dorado‐Morales et al ., 2016; Tanner et al ., 2018; Porcar et al ., 2018). In fact, the microbial communities inhabiting solar panel surfaces around the world are similar in both functional and phylogenetic terms (Tanner et al ., 2018; Porcar et al ., 2018), suggesting the presence of not only common strong selective pressures (leading to functional similarity), but also of common structuring principles (leading to phylogenetic conservation) that include, among others, assembly history (the timing and order in which species arrive) and priority effects (the imprint of arrival order on community structure) (Carlström et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbial composition is characterized by a set of highly resistant bacterial genera ( Deinococcus, Hymenobacter, Roseomonas ) and fungi ( Alternaria , among others), which are marginally present on the panels at the beginning of the experiment, but increase in frequency and become dominant by the end of the experiment. Some of the most abundant bacterial genera, such as Hymenobacter, Modestobacter and Deinococcus , have in fact previously been isolated from warm, irradiated environments, such as arid soil crusts or hyper‐arid desert soils (Reddy and Garcia‐Pichel, 2013; Busarakam et al ., 2016; Gundlapally and Garcia‐Pichel, 2017), and they have also been reported as frequent taxa inhabiting solar panel surfaces (Dorado‐Morales et al ., 2016; Tanner et al ., 2018; Porcar et al ., 2018). In fact, the microbial communities inhabiting solar panel surfaces around the world are similar in both functional and phylogenetic terms (Tanner et al ., 2018; Porcar et al ., 2018), suggesting the presence of not only common strong selective pressures (leading to functional similarity), but also of common structuring principles (leading to phylogenetic conservation) that include, among others, assembly history (the timing and order in which species arrive) and priority effects (the imprint of arrival order on community structure) (Carlström et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant bacterial taxa detected in this work (mean value throughout time) are consistent with those previously described to inhabit solar panel surfaces (Dorado‐Morales et al ., 2016; Tanner et al ., 2018; Porcar et al ., 2018) and other radiation‐exposed environments, suggesting that the strong selection pressure imposed by solar radiation and other factors, such as desiccation, temperature or limited nutrient availability, is what shapes the microbial communities in these environments. For example, a previous study reported that concrete walls exposed to sunlight and ionizing radiation in Chernobyl proved to harbour similar communities to those present in a sun‐exposed environment from a control area (without ionizing radiation), and these were dominated by Actinobacteria , Deinococcales and pigmented ascomycete fungi (Ragon et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA cleanup was then conducted with a fecal DNA extraction kit (ZR Fecal DNA MiniPrep; Zymo Research (Irvine, CA, USA). After DNA extraction, the V3-V4 hypervariable region of the 16S rRNA gene was amplified by polymerase chain reaction and sequenced using the Illumina HiSeq platform (250 base pairs, paired-end reads) as reported previously [16,17].…”
Section: Dna Extraction and 16s Rrna Gene Polymerase Chain Reaction Amentioning
confidence: 99%
“…The DNA cleanup was then conducted with a fecal DNA extraction kit (ZR Fecal DNA MiniPrep; Zymo Research). After DNA extraction, the V3-V4 hypervariable region of the 16S rRNA gene was amplified by polymerase chain reaction and sequenced using the Illumina HiSeq platform (250 base pairs, paired-end reads) as reported previously [10,11].…”
Section: Dna Extraction and 16s Rrna Gene Polymerase Chain Reaction Amentioning
confidence: 99%